Artificial Intelligence in Early Childhood Education: Opportunities and Challenges (Global Journal of Human-Social Science, 2025)
With the continuous advancement of artificial intelligence AI its application within the field of education is becoming increasingly widespread particularly in early childhood education This article first explores the various applications of AI in this domain AI enhances early childhood education by providing a richer and more adaptive learning experience through tools such as intelligent toys and smart learning platforms which offer personalized learning paths interactive educational resources and data analytics The integration of AI not only fosters children s cognitive development language skills and social abilities but also equips educators with powerful tools to enhance their teaching effectiveness and classroom management However incorporating AI into early childhood education presents several challeng es Data privacy and security concerns are paramount underscoring the critical importance of safeguarding children s information Furthermore effectively integrating technology into educational practices necessitates interdisciplinary expertise along with ongoing professional development for teachers Additionally there is a risk that children may become overly reliant on technology thus it is essential to strike a balance between technological use and real-world interactions
Keywords: artificial intelligence; early childhood education; opportunity; challenge